2007
DOI: 10.1038/ni1451
|View full text |Cite
|
Sign up to set email alerts
|

Smad7 binds to the adaptors TAB2 and TAB3 to block recruitment of the kinase TAK1 to the adaptor TRAF2

Abstract: Transforming growth factor-beta1 (TGF-beta1) regulates inflammation and can inhibit activation of the transcription factor NF-kappaB in certain cell types. Here we show that the TGF-beta-induced signaling protein Smad7 bound to TAB2 and TAB3, which are adaptors that link the kinase TAK1 to 'upstream' regulators in the proinflammatory tumor necrosis factor (TNF) signaling pathway. Smad7 thereby promoted TGF-beta-mediated anti-inflammatory effects. The formation of Smad7-TAB2 and Smad7-TAB3 complexes resulted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
101
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 131 publications
(108 citation statements)
references
References 43 publications
5
101
0
2
Order By: Relevance
“…Second, we provide further evidence for a distinct role of Smad6 from Smad7, although both are anti-inflammatory mediators. Previously, only Smad7 was found to be involved in the negative regulation of TNF-α signalling 5 . In this study, we found that TGF-β1-induced ubiquitin-mediated degradation of MyD88 is dependent on the presence of Smad6, but not Smad7.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, we provide further evidence for a distinct role of Smad6 from Smad7, although both are anti-inflammatory mediators. Previously, only Smad7 was found to be involved in the negative regulation of TNF-α signalling 5 . In this study, we found that TGF-β1-induced ubiquitin-mediated degradation of MyD88 is dependent on the presence of Smad6, but not Smad7.…”
Section: Discussionmentioning
confidence: 99%
“…Lentiviruses expressing shRNAs specific for endogenous SMAD7 were previously described 4,5 . To generate shRNAs specific for endogenous SMAD6, SMURF1, SMURF2 and MYD88, double-stranded oligomers containing restriction enzyme sites, a sense sequence, and a loop sequence with its antisense sequence were designed and cloned into AgeI and EcoRI sites of the pLKO-puro vector (Clontech).…”
Section: Construction Of Small Hairpin Rnas and Lentiviral Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 We have shown that keratinocyte-specific Smad7 overexpression causes a reduction in keratinocyte-produced inflammatory cytokines. 13 To determine whether this Smad7 function af- role in wound healing, 27,28 were still present ( Figure 5A). Similar changes lasted till day 9 after wounding; thereafter, leukocyte infiltration was significantly reduced to normal level in either control or Smad7 tg skin (not shown).…”
Section: Inflammation Angiogenesis and Collagen Production Are Redumentioning
confidence: 99%
“…Additionally, the effect of Smad7 may not always be explained by its role in TGF␤ signaling. For instance, Smad7 also interacts with components of the Wnt/␤-catenin 12 and the tumor necrosis factor-␣/nuclear factorkappa B (NF-B) 13 families.…”
mentioning
confidence: 99%